Viscosity reduction type concrete super plasticizer as well as preparation method and application thereof

By using a reducing viscosity-reducing concrete superplasticizer prepared by radical polymerization under microwave conditions in concrete, the problems of large concrete viscosity and slow flow rate are solved, and the concrete viscosity is significantly reduced and the working performance is improved.

CN119912649APending Publication Date: 2025-05-02BOTE BUILDING MATERIALS (TIANJIN) CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411867665.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In the prior art, concrete has a high viscosity and slow flow rate, which leads to increased pumping and construction difficulties of high-rise and large-span concrete, and methods of reducing viscosity may affect the durability of concrete.

Method used

A deviscopic-reducing concrete superplasticizer prepared by radical polymerization under microwave conditions by unsaturated monomers a, b, and c is used. The superplasticizer introduces a methylallyl structure, a rigid ring structure and a branched side chain structure to increase the thickness of the water film layer and improve the viscosity of the concrete.

Benefits of technology

Significantly reduce the viscosity of concrete, improve the working performance of concrete, enhance its dispersion performance and durability, while reducing transportation costs and improving cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005194868420000021
    Figure BDA0005194868420000021
  • Figure BDA0005194868420000031
    Figure BDA0005194868420000031
  • Figure BDA0005194868420000032
    Figure BDA0005194868420000032
Patent Text Reader

Abstract

The invention provides a viscosity reduction type concrete super plasticizer and a preparation method and application thereof.The super plasticizer is solid and is prepared from an unsaturated monomer a, an unsaturated monomer b and an unsaturated monomer c through free radical polymerization under the microwave condition, the unsaturated monomer a is methacrylic acid or methyl alkenyl phosphonic acid monomer, and the unsaturated monomer b is methacrylic acid or methyl alkenyl phosphonic acid monomer. The unsaturated monomer b is a monomer containing a rigid ring, the rigid ring is an aromatic ring or an imidazole ring or a pyridine ring, and the unsaturated monomer c is an unsaturated polyether monomer containing a benzene ring. A methyl group and a rigid ring group are introduced into a main chain of the super plasticizer, so that the rigidity of a polymer is improved, the hydrophobicity is increased, the conformation of the polymer is changed, and a relatively thick water film layer is formed on the surface of cement particles; meanwhile, a branched structure side chain is introduced into the super plasticizer, so that the molecular size of the polymer can be remarkably increased, the steric hindrance effect of the polymer is more outstanding, the dispersing capacity is good, the thickness of a water film layer on the surface of cement can be increased, and the viscosity of concrete is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, and in particular to a viscosity-reducing concrete superplasticizer and a preparation method and application thereof. Background Art

[0002] With the development of high-rise and large-span buildings, the superiority of high-strength concrete and ultra-high-strength concrete has become more prominent. The main means to achieve high-strength and ultra-high-strength concrete are to reduce the water-cement ratio, increase the amount of cementitious materials and optimize mineral admixtures. The water-cement ratio is reduced, the viscosity of concrete increases, and the use of a large amount of machine-made sand is not used for pumping and construction of high-rise concrete due to its many edges and corners, poor grading, high viscosity of concrete, slow flow rate and other prominent problems. At present, the viscosity is reduced by adjusting the mix ratio of admixtures, adding viscosity-reducing water-reducing agents and a small amount of air-entraining agents. A small amount of air-entraining agents can introduce tiny bubbles and reduce the friction between aggregate particles, but using too much will affect the durability of concrete. Viscosity-reducing water-reducing agents can form a thicker water film layer on the surface of cement particles, thereby reducing the viscosity of concrete. Therefore, the application of viscosity-reducing water-reducing agents provides material support for high-strength and ultra-high-strength concrete.

[0003] Patent 2018115981696 provides a method for preparing a viscosity-reducing polycarboxylic acid water-reducing agent containing an alkyl group, that is, a large amount of hydrophobic alkyl groups are introduced into the PEG side chain, which may reduce the solubility of the side chain, reduce the size of the side chain, weaken the steric hindrance effect, and further affect the polymerization activity of the macromonomer.

[0004] Patent 2016100279184 provides a method for preparing a viscosity-reducing polycarboxylic acid water-reducing agent, in which a special vinylbenzyldialkylamine monomer is introduced into the polymer main chain to adjust the polymer conformation, thereby achieving the purpose of viscosity reduction. This method is simple and convenient, but the amount of monomer should not be too much, as too much will disperse the density of the carboxyl groups on the main chain and affect the dispersion ability.

[0005] Patent 2021115619688 discloses a viscosity-reducing polycarboxylic acid water-reducing agent and a preparation method thereof. The viscosity-reducing polycarboxylic acid water-reducing agent of the present invention is obtained by copolymerizing intermediate C obtained by amide / imidization reaction of compound A and compound B, and intermediate C is obtained by copolymerization reaction with monomer D, monomer E, and monomer F; the compound A is an amino polyether, and the compound B is a carboxylic acid containing a thiol group; the monomer D is an unsaturated carboxylic acid, the monomer E is a polymerizable sulfonic acid monomer, and the monomer F is a polymerizable phosphonic acid monomer. The viscosity-reducing polycarboxylic acid water-reducing agent product prepared by the present invention has the advantages of low dosage, high water reduction rate, small slump loss, and especially significantly reducing the viscosity of the slurry at a low water-binder ratio. Summary of the invention

[0006] In view of the above-mentioned series of problems such as high viscosity and slow flow rate of concrete in the prior art, this application proposes a viscosity-reducing concrete superplasticizer and its preparation method and application. The rigid ring group is introduced into the structure of the superplasticizer in this application, which can stretch the molecular conformation of the polymer, thereby increasing the thickness of the water film layer; the methyl allyl structure is more rigid than the corresponding vinyl structure because the free rotation of the molecular chain is hindered; at the same time, the branched side chain in the polymer can increase the molecular size of the polymer compared to the linear structure, which can increase the thickness of the water film layer formed by the polymer on the cement surface, thereby improving the viscosity of the concrete.

[0007] A viscosity-reducing concrete superplasticizer is solid and is prepared by free radical polymerization of unsaturated monomer a, unsaturated monomer b and unsaturated monomer c under microwave conditions; the weight average molecular weight of the superplasticizer is 10000-50000.

[0008] The molar ratio of the unsaturated monomer a:unsaturated monomer b:unsaturated monomer c is (1-8):(0.05-0.5):1;

[0009] The structural formula of the unsaturated monomer a is shown in the following formula (1):

[0010]

[0011] Wherein, R1, R2, and R3 are independently H or CH3, and R1, R2, and R3 are not H at the same time, and A is a structure containing a carboxyl group or a phosphate group;

[0012] Preferably, the above monomer a is methacrylic acid or methyl vinylphosphonic acid monomer;

[0013] The methyl vinylphosphonic acid monomer is prepared from the corresponding substrate containing amino or hydroxyl groups by known methods. For monomers containing amino substrates, monomer a is synthesized by Mannich reaction, and for monomers containing hydroxyl substrates, monomer a is prepared by reacting with phosphoric acid, and these preparation methods are all known methods in the prior art. The substrate used is selected from but not limited to methyl allyl alcohol, monomethyl allyl glycol ether, 4-methyl-4-pentene-1-ol, 3-methyl-4-pentene-1-ol, and 2-methylallylamine.

[0014] The molecular chain of methyl allyl group has high rigidity, which can adjust the conformation of the polymer, and then regulate the adsorption form of the polymer on cement particles, affecting the dispersion ability of the polymer.

[0015] The unsaturated monomer b is a monomer containing a rigid ring, and the rigid ring is an aromatic ring, an imidazole ring, or a pyridine ring;

[0016] The structural formula of the unsaturated monomer b is as shown in the following formula (2), (3) or (4):

[0017]

[0018] R4 is H or CH3; R5, R6, R7 are H, CH3, OCH3, CH2CH3, SO3, -NH2, -COOH;

[0019] The unsaturated monomer b is selected from at least one of 1-vinylimidazole, 2-methyl-1-vinylimidazole, 2-vinylpyridine, 3-vinylpyridine, 4-vinylpyridine, 3-methyl-5-vinylpyridine, 3-vinylbenzoic acid, 4-vinylbenzoic acid, 3-vinylaniline, 4-vinylaniline, 3-vinylbenzylamine, 4-vinylbenzylamine, N-vinylpyrrolidone, vinylbenzyl alcohol, p-vinylphenylethanol, sodium styrene sulfonate, and p-aminostyrene.

[0020] The rigid groups in the structure of unsaturated monomer b can well adjust the conformation and hydrophilicity of the polymer, and then adjust the air content and state of the concrete. However, if the content is too high, the adsorption groups of the polymer will be severely diluted, affecting its dispersion performance.

[0021] The above unsaturated monomer c is an unsaturated polyether monomer containing a benzene ring;

[0022] The structural formula of the unsaturated monomer c is shown in the following formula (5):

[0023]

[0024] Wherein, AO is an oxyalkylene group of 2-4 carbon atoms or a mixture of two or more oxyalkylene groups, n is the average added mole number of AO, which is an integer of 10-60; (AO)n is a homopolymer, random copolymer, diblock or multiblock copolymer structure.

[0025] The unsaturated monomer c is prepared by an alkoxylation reaction of unsaturated monomer p-vinylbenzylamine with alkylene oxide under the conditions of a catalyst and an inhibitor. The alkoxylation reaction temperature is 110-150°C, and the reaction pressure is 0.1-0.6MPa. After the alkoxylation reaction, the product has a strong alkalinity. For the convenience of storage, the product needs to be neutralized and post-treated. The neutralization temperature is maintained at 60-90°C. If the temperature is too low, the product has a large viscosity and is difficult to neutralize. If the temperature is too high, more by-products are produced. The organic acid used for neutralization can be selected from any one of oxalic acid, glacial acetic acid, and citric acid, and the organic acid is used to neutralize to about pH=7.

[0026] The side chain formed after the unsaturated monomer c participates in the polymerization is a branched structure, which has a greater steric hindrance effect and forms a thicker water film layer, which can not only play a good role in dispersion and dispersion retention, but also can adjust the viscosity of the configured concrete.

[0027] The catalyst is selected from any one of metallic sodium, metallic potassium, sodium methoxide, potassium methoxide, sodium ethoxide, potassium ethoxide, sodium hydroxide, potassium hydroxide, sodium hydride, potassium hydride, sodium naphthalene and potassium naphthalene, and the amount of the catalyst used is 0.01%-0.5% of the mass of the final polyether monomer c.

[0028] The above-mentioned inhibitor is at least one of 2-sec-butyl-4,6-dinitrophenol (DNBP), N-{4-[(1,3-dimethylbutyl)imino]-2,5-cyclohexadiene} (BDQI), 2,6-di-tert-butyl-4-benzylidene-cyclohexa-2,5-dienone, 2,2-diphenyl-1-picrylhydrazyl (DPPH), N,N-dihydroxypropylhydroxylamine, N-methyl-2-pyrrolidone (NMP), dodecylbenzenesulfonic acid, and 2,4-dinitro-p-cresol (DNPC), and the amount of the inhibitor is 0.001%-0.1% of the mass of the polyether monomer c.

[0029] A method for preparing a viscosity-reducing concrete superplasticizer comprises the following steps: uniformly mixing unsaturated monomer a, unsaturated monomer b, unsaturated monomer c and a chain transfer agent, placing the mixture in a microwave reactor and heating the mixture to 60-100 DEG C to make the mixture reach a molten state, reacting the mixture for 1-3 hours, adding an initiator in small amounts and multiple times (5-8 times evenly divided within a dropwise addition time of 1-3 hours), carrying out a free radical polymerization reaction, keeping the mixture warm for 1-2 hours after the dropwise addition is completed, cooling the mixture and slicing the mixture with a condensation slicer to obtain a superplasticizer.

[0030] The chain transfer agent is a thiol polymer chain transfer agent, which is selected from at least one of mercaptopropionic acid, mercaptoethanol, thioglycolic acid, sodium thioglycolate, isooctyl thioglycolate, mercaptoethylamine and dodecanethiol; the amount of the chain transfer agent is 0.5-3.0% of the total mass of the unsaturated monomer a, the unsaturated monomer b and the unsaturated monomer c.

[0031] The initiator is selected from at least one of potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisoheptanenitrile, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride, and azoisobutylcyanoformamide. The oxidant is used in an amount of 0.5-2.0% of the total mass of the unsaturated monomer a, the unsaturated monomer b, and the unsaturated monomer c.

[0032] The amount of superplasticizer is 0.1-0.5% of the total mass of the cementitious material. Preferably, the amount is 0.15-0.4%. If the amount added is less than 0.1%, the dispersion performance is unsatisfactory; on the contrary, if the amount added exceeds 0.5%, excessive addition will cause serious reverse growth of the mortar, even segregation and bleeding, and increase the construction cost.

[0033] Compared with the prior art, this application has the following advantages:

[0034] (1) The viscosity-reducing superplasticizer of the present application can be used as a dispersant for hydraulic binders and / or potential hydraulic binders. The dispersant has excellent water-reducing performance, can reduce the viscosity of concrete, and improve the working performance of concrete. The production of the dispersant is clean, the production efficiency is high, the transportation cost can be reduced, and the product has a high cost-effectiveness ratio;

[0035] (2) The introduction of methyl and rigid ring groups into the main chain of the superplasticizer of the present application increases the hydrophobicity and changes the conformation of the polymer, so that a thicker water film layer is formed on the surface of cement particles; at the same time, the introduction of branched structure side chains into the superplasticizer can significantly increase the molecular size of the polymer, making its steric hindrance effect more prominent, and having good dispersibility and increasing the thickness of the water film layer on the cement surface. The lubricating effect of the water film layer reduces the friction between cement particles, thereby reducing the viscosity of the concrete;

[0036] The viscosity-reducing superplasticizer provided by the present invention has excellent water-reducing performance and can reduce the viscosity of concrete, especially the viscosity of high-strength / ultra-high-strength concrete; it has good storage stability and low long-distance transportation cost, thereby improving the cost-effectiveness of concrete admixtures. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the embodiments and comparative examples of the present invention, the molecular weight of the polymer refers to the weight average molecular weight, and all molecular weights are measured by Agilent gel permeation chromatography. (Gel column: Shodex SB806+803 two chromatographic columns connected in series; eluent: 0.1M NaNO3 solution; mobile phase speed: 1.0ml / min; injection: 20μl 0.5% aqueous solution; detector: differential refractive index detector; standard: polyethylene glycol GPC standard (Siigma-Aldrich, molecular weight 1010000, 478000, 263000, 118000, 44700, 18600, 6690, 1960, 628, 232).

[0039] The structure of the monomer a used is shown in Table 1 below:

[0040] Table 1

[0041]

[0042]

[0043] Synthesis of monomer a-1

[0044] To a three-necked flask equipped with a stirrer, add 7.2 g (0.1 mol) of methyl allyl alcohol, followed by 13.5 g of phosphoric acid (0.11 mol, 80% aq) and 0.9 g of p-benzoquinone. After adding 50 ml of toluene, install a water separator on the flask, raise the temperature to about 115°C until the solution refluxes, and react for 20-24 hours until no more water is added in the water separator. After the reaction is completed, distill off the azeotrope of toluene and water under reduced pressure to obtain the final product with a yield of 93%.

[0045] Synthesis of monomer a-2

[0046] To a three-necked flask equipped with a stirrer, add 11.6 g (0.1 mol) of monomethyl allyl glycol ether, followed by 13.5 g of phosphoric acid (0.11 mol, 80% aq) and 1.1 g of p-benzoquinone. After adding 50 ml of toluene, install a water separator on the flask, raise the temperature to about 125°C until the solution refluxes, and react for 20-24 hours until no more water continues to increase in the water separator. After the reaction is completed, distill off the azeotrope of toluene and water under reduced pressure to obtain the final product with a yield of about 92%.

[0047] Synthesis of monomer a-3

[0048] To a three-necked flask equipped with a stirrer, add 8.6 g (0.1 mol) of 4-methyl-4-penten-1-ol, followed by 13.5 g of phosphoric acid (0.11 mol, 80% aq) and 0.97 g of p-benzoquinone. After adding 50 ml of toluene, install a water separator on the flask, raise the temperature to about 125°C until the solution refluxes, and react for 20-24 hours until no more water continues to increase in the water separator. After the reaction is completed, distill off the azeotrope of toluene and water under reduced pressure to obtain the final product with a yield of about 94%.

[0049] Synthesis of monomer a-4

[0050] To a three-necked flask equipped with a stirrer, add 7.2 g (0.1 mol) of 4-methyl-3-penten-1-ol, followed by 13.5 g of phosphoric acid (0.11 mol, 80% aq) and 0.97 g of p-benzoquinone. After adding 50 ml of toluene, install a water separator on the flask, raise the temperature to about 120°C until the solution refluxes, and react for 20-24 hours until no more water continues to increase in the water separator. After the reaction is completed, distill off the azeotrope of toluene and water under reduced pressure to obtain the final product with a yield of about 93%.

[0051] Synthesis of monomer a-5

[0052] Into a three-necked flask equipped with a stirrer, 7.1 g (0.1 mol) of 2-methylallylamine, 16.4 g (0.2 mol) of phosphorous acid, and 5.0 g (0.05 mol) of 98% concentrated sulfuric acid were added, and 1.0 g of p-benzoquinone was added. The reaction mixture was heated to 120°C and reacted for 5 hours. 17.0 g (0.21 mol) of 37% formaldehyde aqueous solution was added, and the reaction was heated to reflux for 20 hours. The crude reaction product was washed with methanol for several times, and the methanol and water were distilled off to finally obtain the product. The reaction yield was 96%.

[0053] Monomer b is a commercially available sample, and in the preparation example, b1 is 2-methyl-1-vinylimidazole, b2 is 4-vinylpyridine, b3 is 3-vinylbenzoic acid, b4 is 4-vinylaniline, b5 is 3-vinylbenzylamine, and b6 is N-vinylpyrrolidone.

[0054] Preparation of Monomer C:

[0055] Place p-vinylbenzylamine in a 2L dry stainless steel high-pressure reactor, add appropriate amounts of catalyst and inhibitor, stir and dissolve, close the reactor, replace the air in the reactor with nitrogen three times, then evacuate the reactor to below -0.05MPa, turn on the heating, raise the temperature to 120°C, and keep the reactor evacuated for 30 minutes before stopping, then continue to slowly introduce an appropriate amount of ethylene oxide into the reactor, maintain the pressure in the reactor at 0.15-0.2MPa, and the reaction temperature at 110-150°C. After the addition of ethylene oxide is completed, continue the constant temperature reaction until the pressure no longer decreases, maintain for 30 minutes, evacuate to below -0.008MPa, cool to 60°C, neutralize with glacial acetic acid to about pH=7, and discharge to obtain the desired polyether macromonomer. (Among them, C1 polyether n=10, C2 polyether n=20, C3 polyether n=30, C4 polyether n=40, C5 polyether n=50, C6 polyether n=60).

[0056] Preparation Example 1

[0057] 92.4g (0.4mol) of monomer a5, 2.16g (0.02mol) of monomer b1, 405.2g (0.4mol) of monomer c1 and 14.9g of dodecanethiol are mixed uniformly in proportion and placed in a microwave reactor. The temperature is added to reach 60°C to achieve a molten state. 9.99g of azobisisobutylimidazoline hydrochloride as an initiator is added in 5 equal portions within 1 hour to react. The reaction is continued by keeping the temperature warm for 3 hours, and the mixture is cooled and sliced ​​with a condensation microtome to prepare a solid superplasticizer (the weight average molecular weight of the sample is 13500).

[0058] Preparation Example 2

[0059] 91.2g (0.6mol) of monomer a1, 1.68g (0.016mol) of monomer b2, 378.6g (0.2mol) of monomer c2 and 9.37g of dodecanethiol were mixed uniformly in proportion and placed in a microwave reactor. The temperature was raised to 70°C to achieve a molten state. 7.03g of azobisisobutyronitrile as an initiator was added in 6 equal portions within 1.5h to react. The reaction was continued by keeping the temperature warm for 2.5h. The solid superplasticizer was prepared by cooling and slicing with a condensation microtome (the weight average molecular weight of the sample was 23600).

[0060] Preparation Example 3

[0061] 94.1g (0.48mol) of monomer a2, 1.78g (0.012mol) of monomer b3, 332.7g (0.12mol) of monomer c3 and 8.53g of dodecanethiol were mixed uniformly in proportion and placed in a microwave reactor. The temperature was added to reach 80°C to achieve a molten state. 5.12g of initiator sodium persulfate was added in 6 equal portions within 2h to react. The reaction was continued by keeping the temperature warm for 3h, and the mixture was cooled and sliced ​​with a condensation slicer to prepare a solid superplasticizer (the weight average molecular weight of the sample was 29900).

[0062] Preparation Example 4

[0063] 79.7g (0.48mol) of monomer a3, 2.38g (0.02mol) of monomer b4, 365.3g (0.1mol) of monomer c4 and 6.68g of sodium thioglycolate were mixed uniformly in proportion, placed in a microwave reactor, and added to make its temperature reach 70°C to achieve a molten state. 4.45g of initiator ammonium persulfate was added in 5 equal portions within 2h to react. The reaction was continued by keeping the temperature warm for 2h, cooled and sliced ​​with a condensation microtome to prepare a solid superplasticizer (the weight average molecular weight of the sample is 36800).

[0064] Preparation Example 5

[0065] 99.6 g (0.6 mol) of monomer a4, 4.0 g (0.03 mol) of monomer b5, 453.3 g (0.1 mol) of monomer c5 and 5.55 g of mercaptopropionic acid were mixed uniformly in proportion, placed in a microwave reactor, and added to make its temperature reach 100° C. to reach a molten state, and 4.44 g of initiator sodium persulfate was added in 8 equal portions within 2.5 hours to react, and the mixture was kept warm for 2 hours. The mixture was cooled and sliced ​​with a condensation slicer to prepare a solid superplasticizer (the weight average molecular weight of the sample was 43500).

[0066] Preparation Example 6

[0067] 106.2g (0.64mol) of monomer a5, 4.44g (0.04mol) of monomer b6, 433.0g (0.08mol) of monomer c6 and 2.71g of mercaptoethanol were mixed uniformly in proportion, placed in a microwave reactor, and added to make its temperature reach 75°C to reach a molten state. 2.71g of initiator ammonium persulfate was added in 4 equal portions within 1h to react. The mixture was kept warm for 2h, cooled and sliced ​​with a condensation microtome to prepare a solid superplasticizer (the weight average molecular weight of the sample was 49800).

[0068] Preparation Example 7

[0069] 51.6g (0.6mol) of monomer a6, 1.77g (0.012mol) of monomer b3, 438.4g (0.12mol) of monomer c4 and 7.35g of dodecanethiol were mixed uniformly in proportion, placed in a microwave reactor, and added to make its temperature reach 60°C to achieve a molten state. 5.89g of azobisisobutylimidazoline hydrochloride as an initiator was added in 8 equal portions within 3h to react. After the addition was completed, the mixture was kept warm for 2h, cooled and sliced ​​with a condensation microtome to prepare a solid superplasticizer (the weight average molecular weight of the sample was 34600).

[0070] Comparative Preparation Example 1

[0071] 43.2g (0.6mol) of acrylic acid, 1.77g (0.012mol) of monomer b3, 438.4g (0.12mol) of monomer c4 and 7.35g of dodecanethiol were mixed uniformly in proportion, placed in a microwave reactor, and added to make its temperature reach 60°C to achieve a molten state. 5.89g of azobisisobutylimidazoline hydrochloride as an initiator was added in 8 equal portions within 3h to react. After the addition was completed, the mixture was kept warm for 2h, cooled and sliced ​​with a condensation microtome to prepare a solid superplasticizer (the weight average molecular weight of the sample was 31500).

[0072] Comparative Preparation Example 2

[0073] 51.6g (0.6mol) of monomer a6, 1.77g (0.012mol) of monomer b3, 438.4g (0.12mol) of p-vinylbenzyl polyoxyethylene ether (molecular weight consistent with C4) and 7.35g of dodecanethiol are mixed evenly in proportion, placed in a microwave reactor, and added to make its temperature reach 60°C to reach a molten state, and 5.89g of azobisisobutylimidazoline hydrochloride as initiator is added in 8 equal portions within 3h to react. After the addition is completed, the mixture is kept warm for 2h, cooled and sliced ​​with a condensation microtome to prepare a solid superplasticizer (the weight average molecular weight of the sample is 36800).

[0074] Comparative Preparation Example 3

[0075] 51.6g (0.6mol) of monomer a6, 438.4g (0.12mol) of monomer c4 and 7.35g of dodecanethiol were mixed uniformly in proportion, placed in a microwave reactor, and added to make its temperature reach 60°C to reach a molten state. 5.89g of azobisisobutylimidazoline hydrochloride as initiator was added in 8 equal portions within 3h to react. After the addition was completed, the mixture was kept warm for 2h, cooled and sliced ​​with a condensation microtome to prepare a solid superplasticizer (the weight average molecular weight of the sample was 33500).

[0076] Test Example 1: Cement paste fluidity test

[0077] The cement paste fluidity test was carried out in accordance with GB / T 8077 standard, using Onoda cement 52.5R PⅡ, with a water addition of 87g, and the cement paste fluidity on the flat glass was tested according to the operating procedures, and the initial fluidity of the cement paste fluidity was controlled at 260-280mm. The clay of the cement paste was referenced to GB / T10274 "Viscosity Measurement Method", and the commercially available sample was a water reducer SBT-PCA1 (weight average molecular weight of 32200). The experimental results are shown in Table 2.

[0078] Table 2 Cement paste fluidity test results

[0079]

[0080]

[0081] From the test results in Table 2, it can be found that the apparent viscosity of the cement paste configured with the viscosity-reducing superplasticizer prepared by the present invention is relatively small, while after replacing or eliminating some raw materials in the control ratio, the apparent viscosity of the cement paste increases, and the viscosity of the paste fluidity configured with the conventional water reducer on the market is far greater than the viscosity configured with the sample of the present invention.

[0082] Test Example 2: Concrete Performance Test

[0083] The slump and expansion of ultra-high performance concrete are tested according to the method specified in GB50080-2016 "Standard for Performance Test Methods of Ordinary Concrete Mixtures"; the flow time t of concrete is tested according to the method specified in CECS203-2006 "Technical Specifications for the Application of Self-compacting Concrete": turn the slump bucket upside down, cover the bottom, fill it with concrete and smooth it, quickly slide the bottom cover open, and use a stopwatch to record the concrete flow time t. The longer the time, the greater the viscosity of the concrete. The cement used is Onoda Cement 52.5R PⅡ, fly ash: Class II ash; sand: machine-made sand, fineness modulus 2.6, gravel: 5-25mm continuously graded crushed stone. The mix ratio used (kg / m 3) is cement: fly ash: mineral powder: sand: crushed stone: water = 400:40:50:30:684:1128:138, and the commercially available sample is water reducer SBT-PCA1 (weight average molecular weight is 32200). The test results are shown in Table 3:

[0084] Table 3 Concrete test results

[0085]

[0086] The viscosity-reducing concrete superplasticizer synthesized in the present application has good dispersibility, and the collapse time of the configured concrete is short, indicating that the introduction of methyl olefin structure, rigid ring structure and branched side chain structure into the superplasticizer can effectively reduce the viscosity of concrete. Compared with conventional commercially available samples, the samples of the present application can effectively reduce the viscosity of concrete.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A viscosity-reducing concrete superplasticizer, characterized in that: The superplasticizer is solid and is prepared by free radical polymerization of unsaturated monomer a, unsaturated monomer b and unsaturated monomer c under microwave conditions; the molar ratio of unsaturated monomer a: unsaturated monomer b: unsaturated monomer c is (1-8): (0.05-0.5): 1; The structural formula of the unsaturated monomer a is shown in the following formula (1); Wherein, R1, R2, and R3 are independently H or CH3, and R1, R2, and R3 are not H at the same time, and A is a structure containing a carboxyl group or a phosphate group; The unsaturated monomer b is a monomer containing a rigid ring, and the rigid ring is an aromatic ring, an imidazole ring, or a pyridine ring; The structural formula of the unsaturated monomer b is as shown in the following formula (2), (3) or (4): R4 is H or CH3; R5, R6, R7 are H, CH3, OCH3, CH2CH3, SO3, -NH2, -COOH; The unsaturated monomer c is an unsaturated polyether monomer containing a benzene ring; The weight average molecular weight of the superplasticizer is 10,000-50,000.

2. The viscosity-reducing concrete superplasticizer according to claim 1, characterized in that: The unsaturated monomer b is selected from at least one of 1-vinylimidazole, 2-methyl-1-vinylimidazole, 2-vinylpyridine, 3-vinylpyridine, 4-vinylpyridine, 3-methyl-5-vinylpyridine, 3-vinylbenzoic acid, 4-vinylbenzoic acid, 3-vinylaniline, 4-vinylaniline, 3-vinylbenzylamine, 4-vinylbenzylamine, N-vinylpyrrolidone, vinylbenzyl alcohol, p-vinylphenylethanol, sodium styrene sulfonate, and p-aminostyrene.

3. The viscosity-reducing concrete superplasticizer according to claim 1, characterized in that: The structural formula of the unsaturated monomer c is shown in the following formula (5): Wherein, AO is an oxyalkylene group of 2-4 carbon atoms or a mixture of two or more oxyalkylene groups, n is the average added mole number of AO, which is an integer of 10-60; (AO)n is a homopolymer, random copolymer, diblock or multiblock copolymer structure.

4. The viscosity-reducing concrete superplasticizer according to claim 3, characterized in that: The unsaturated monomer C is prepared by an alkoxylation reaction between unsaturated monomer p-vinylbenzylamine and alkylene oxide in the presence of a catalyst and a polymerization inhibitor.

5. The viscosity-reducing concrete superplasticizer according to claim 4, characterized in that: The catalyst is selected from any one of metallic sodium, metallic potassium, sodium methoxide, potassium methoxide, sodium ethoxide, potassium ethoxide, sodium hydroxide, potassium hydroxide, sodium hydride, potassium hydride, sodium naphthalene and potassium naphthalene, and the amount of the catalyst is 0.01%-0.5% of the mass of the polyether monomer C.

6. The viscosity-reducing concrete superplasticizer according to claim 4, characterized in that: The polymerization inhibitor is at least one of 2-sec-butyl-4,6-dinitrophenol, N-{4-[(1,3-dimethylbutyl)imino]-2,5-cyclohexadiene}, 2,6-di-tert-butyl-4-benzylidene-cyclohexa-2,5-dienone, 2,2-diphenyl-1-picrylhydrazine, N,N-dihydroxypropylhydroxylamine, N-methyl-2-pyrrolidone, dodecylbenzenesulfonic acid, and 2,4-dinitro-p-cresol, and the dosage of the polymerization inhibitor is 0.001%-0.1% of the mass of the polyether monomer c.

7. The method for preparing a viscosity-reducing concrete superplasticizer according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing unsaturated monomer a, unsaturated monomer b, unsaturated monomer c and a chain transfer agent, placing the mixture in a microwave reactor and heating the mixture to 60-100° C. to make the mixture reach a molten state, reacting the mixture for 1-3 hours, adding an initiator in small amounts and multiple times to carry out a free radical polymerization reaction, keeping the mixture warm for 1-2 hours after the addition is completed, cooling the mixture and slicing the mixture with a condensation slicer to obtain a superplasticizer.

8. The preparation method according to claim 7, characterized in that: The chain transfer agent is a thiol polymer chain transfer agent, and the thiol polymer chain transfer agent is selected from at least one of mercaptopropionic acid, mercaptoethanol, thioglycolic acid, sodium thioglycolate, isooctyl thioglycolate, mercaptoethylamine and dodecanethiol; the amount of the chain transfer agent is 0.5-3.0% of the total mass of the unsaturated monomer a, the unsaturated monomer b and the unsaturated monomer c.

9. The preparation method according to claim 7, characterized in that: The initiator is selected from at least one of potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisoheptylonitrile, azobisisobutyramidine hydrochloride, azobisisobutylimidazoline hydrochloride, and azoisobutylcyanoformamide. The amount of the oxidant is 0.5-2.0% of the total mass of the unsaturated monomer a, the unsaturated monomer b, and the unsaturated monomer c.

10. An application of a viscosity-reducing concrete superplasticizer, characterized in that: The superplasticizer dosage is 0.1-0.5% of the total gelling material mass; the superplasticizer is the superplasticizer described in any one of claims 1-6 or the superplasticizer obtained by the preparation method described in any one of claims 7-9.

Citation Information

Cited By

  • High-workability concrete super plasticizer as well as preparation method and application thereof

    CN120574354A